2005
DOI: 10.1007/s10452-004-5732-0
|View full text |Cite
|
Sign up to set email alerts
|

An in situ method for the investigation of vertical distributions of zooplankton in lakes: test of a two-compartment enclosure

Abstract: Two-section enclosures were designed for the investigation of the effect of various physicochemical and biological factors on vertical distribution of zooplankton in situ. The framework of the enclosure was a cylindrical polyethylene column without any partitions inside, in which the isolation of animals in different sections after in situ exposure was achieved by pinching the flexible central part of the column. Enclosures were tested at the brackish stratified meromictic Lake Shira (Russia, Khakasia). The ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Thermal stratification and associated physicochemical gradients have been shown to influence patterns of depth selection and vertical distribution of crustacean zooplankton in stratified lakes (Winder, Buergi & Spaak, 2003; Thackeray et al. , 2006; Johnson, O’Brien & MacIntyre, 2007) and enclosure experiments (Tolomeyev & Zadereev, 2005). In deep lakes, stratification exposes zooplankton to sharp vertical gradients in light, temperature, oxygen, food concentrations and predation risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal stratification and associated physicochemical gradients have been shown to influence patterns of depth selection and vertical distribution of crustacean zooplankton in stratified lakes (Winder, Buergi & Spaak, 2003; Thackeray et al. , 2006; Johnson, O’Brien & MacIntyre, 2007) and enclosure experiments (Tolomeyev & Zadereev, 2005). In deep lakes, stratification exposes zooplankton to sharp vertical gradients in light, temperature, oxygen, food concentrations and predation risk.…”
Section: Introductionmentioning
confidence: 99%
“…In lake ecosystems, habitat complexity arises as the result of vertical and horizontal structuring of freshwater habitats and is reflected in the distribution patterns of zooplankton (Pinel-Alloul, 1995;Pinel-Alloul & Ghadouani, 2007). Thermal stratification and associated physicochemical gradients have been shown to influence patterns of depth selection and vertical distribution of crustacean zooplankton in stratified lakes (Winder, Buergi & Spaak, 2003;Thackeray et al, 2006;Johnson, O'Brien & MacIntyre, 2007) and enclosure experiments (Tolomeyev & Zadereev, 2005). In deep lakes, stratification exposes zooplankton to sharp vertical gradients in light, temperature, oxygen, food concentrations and predation risk.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the epilimnion population of A. salinus must migrate to these deeper waters to maintain in their bodies the observed levels of these acids. This argument, however, is not supported by Tolomeyev and Zadereev (2005) who found that diel vertical migration of A. salinus in Lake Shira is weakly pronounced due to the absence of predators for zooplankton. Nevertheless, the difference between day and nighttime distribution profiles of A. salinus does comprise its lower day-time density in the upper (1 m) layer probably due to a negative phototactic response to intensive solar radiation.…”
Section: Fatm In Tag and Feeding Experiments As Indicators Of The Diementioning
confidence: 77%